Can public opinion about Western Sahara’s Cause be revealed by Social Media data analysis? - Guedes, Ana Maria (Africana Studia, 2020)
This study intends to test the use of Big Data sources, in this case Twitter data, as a reliable source for tracking opinions related to Western Sahara self-determination. These data provide indicators of national trends of public opinion, which can be compared with the respective government policies regarding the Western Sahara conflict. Keywords: Social N etworks, Twitter, s entiment analysis, Western Sahara.